ON THE SPOTTEDNESS OF RED DWARF STARS - Alekseev, I. Yu.; Gershberg, R. E. (Одеські астрономічні публікації, 2017)
A new approach for analysis of the spotteduess of red dwarfs based on their multicolor photometry is shortly described and main results of such an analysis are presented. ON THE SPOTTEDNESS OF RED DWARF STARS